Analysis of Clean Water Supply Needs In Mengkendek District, Tana Toraja Regency - Hardianto Pabilang; Baharuddin Hamzah; Samsuddin Samsuddin (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
The coverage of clean water services from PDAM in Mengkendek District, Tana Toraja Regency in 2022 is 6.07%, so there are still 93.93% of the population who cannot be served. This condition will worsen as water demand increases every year. This study aims to determine the scope of services, maximum water needs, water balance and clean water potential, so that it is expected to answer the problems to be discussed. The study began by calculating population growth over the next 20 years. The mathematical model used is the Exponential Model. This model is selected taking into account the resulting Standard Deviation and Correlation Coefficient. The calculation of water needs is obtained from the needs of the number of customers. Furthermore, water needs will be linked to the production capacity plan so as to produce a water balance. Water demand in 2023 is 85 liters/s and will increase in the following year until in 2042 water demand reaches 148 liters/s. The water balance is in deficit at the moment. Answering this, researchers made observations to determine the potential of clean water sources that can be used for the development of clean water supply systems in Mengkendek District, Tana Toraja Regency. The observation results show that there is a potential river water discharge of 23.21 m3 / s or 23,214 lps that can be utilized. By utilizing this potential, 90% service coverage until 2042 can be achieved.